Positive harmony transformations and equilibrium selection in two-player games - Zizzo, D (University of Oxford, 2004)
Game harmony is a generic game property that describes how harmonious (non-conflictual) or disharmonious (conflictual) the interests of players are, as embodied in the payoffs. It can be used to predict cooperation in two-player games. We show how, for large enough positive harmony transformations of the game, a utilitarian solution is always a Nash equilibrium, coincides with the Nash bargaining solution and acquires further desirable properties of payoff and risk dominance. Case-based reasoning and team reasoning are alternative mechanisms by which game harmony measures can successfully predict cooperative behavior.